PENINGKATAN KEMAMPUAN PUBLIC SPEAKING MELALUI BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA - Achmad Abdul Wahid; Indah Lestari; Gudnanto Gudnanto (Universitas Muria Kudus, 2022)
Research objectives: 1. Describe the implementation of Group guidance with sociodrama techniques to improve public speaking skills of students of Grade XI mathematics and Natural Sciences 3 SMA Negeri 1 Kayen. 2. To obtain an increase in public speaking skills through Group guidance services with sociodrama techniques in students of Grade XI mathematics and Natural Sciences 3 SMA Negeri 1 Kayen. This study uses the design of guidance and Action Research (PTBK) conducted with two cycles, cycle I followed by Cycle II. While this study uses descriptive qualitative methods. Where the results of research conducted by researchers in the form of a description or description using words or sentences. Based on the results of research that has been done in the first cycle and the second cycle can be seen that the guidance service group sociodrama techniques can improve the ability of public speaking in Class XI SMA Negeri 1 Kayen accepted because it has achieved indicators of success.